Novel Alleles of Phosphorus-Starvation Tolerance 1 Gene (PSTOL1) from Oryza rufipogon Confers High Phosphorus Uptake Efficiency - Neelam, Kumari; Thakur, Shiwali; Neha; Yadav, Inderjit S.; Kumar, Kishor; Dhaliwal, Salwinder S.; Singh, Kuldeep (Frontiers in Plant Science, 2017)
ABSTRACT Limited phosphorus availability in the soil is one of the major constraints to the growth and productivity of rice across Asian, African and South American countries, where 50% of the rice is grown under rain-fed systems on poor and problematic soils. With an aim to determine novel alleles for enhanced phosphorus uptake efficiency in wild species germplasm of rice Oryza rufipogon, we investigated phosphorus uptake1 (Pup1) locus with 11 previously reported SSR markers and sequence characterized the phosphorus-starvation tolerance 1 (PSTOL1) gene. In the present study, we screened 182 accessions of O. rufipogon along with Vandana as a positive control with SSR markers. From the analysis, it was inferred that all of the O. rufipogon accessions undertaken in this study had an insertion of 90 kb region, including Pup1-K46, a diagnostic marker for PSTOL1, however, it was absent among O. sativa cv. PR114, PR121 and PR122. The complete PSTOL1 gene was also sequenced in 67 representative accessions of O. rufipogon and Vandana as a positive control. From comparative sequence analysis, 53 mutations (52 SNPs and 1 nonsense mutation) were found in the PSTOL1 coding region, of which 28 were missense mutations and 10 corresponded to changes in the amino acid polarity. These 53 mutations correspond to 17 haplotypes, of these 6 were shared and 11 were scored only once. A major shared haplotype was observed among 44 accessions of O. rufipogon along with Vandana and Kasalath. Out of 17 haplotypes, accessions representing 8 haplotypes were grown under the phosphorus-deficient conditions in hydroponics for 60 days. Significant differences were observed in the root length and weight among all the genotypes when grown under phosphorus deficiency conditions as compared to the phosphorus sufficient conditions. The O. rufipogon accession IRGC 106506 from Laos performed significantly better, with 2.5 times higher root weight and phosphorus content as compared to the positive control Vandana. In terms of phosphorus uptake efficiency, the O. rufipogon accessions IRGC 104639, 104712 and 105569 also showed nearly two times higher phosphorus content than Vandana. Thus, these O. rufipogon accessions could be used as the potential donor for improving phosphorus